Hedging in academic writing: the use of “can” in university students’ argumentative essays at an English Medium University in Turkey - Tıkaç, Saadet. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2013., 2013)
This study aims to shed light on the ways of using hedging devices in academic writing by a group of first year university students studying in the department of English language education at a Turkish state university. The main objective of this study is to explore the nature of hedges and modal auxiliaries with a specific focus on the use of “can” as a hedging device in students’ argumentative essays. The secondary focus of the study is to investigate how student writers build their authorial stance in regard to the argument they develop in their texts. The first data set of the study comprises 22 argumentative essays. The data are collected in the English Composition class. The second data set comprises interviews with the aforementioned student writers who participated in the study. The first data set was analyzed both manually and with the “Simple Concordancing Program”. The second data set was transcribed and analyzed with the qualitative research analysis software, “NVivo”. The results of the study revealed that Turkish students had a tendency to hide their authorial stance with regard to the argument they developed in their essays through use of various hedging devices. When the functions of the modal verb “can” were analyzed, it was observed that the frequency of use of “can” as an ability marker was higher than the use of “can” as a possibility marker. In addition, in the interviews, the students stated that they did not receive explicit instruction on different functions of “can” except its use as an ability marker in their earlier English language learning experience.
Keywords: College readers.; Interdisciplinary approach in education -- Problems, exercises, etc.; English language -- Rhetoric -- Problems, exercises, etc.; Academic writing -- Problems, exercises, etc.